2003
DOI: 10.1002/elps.200305464
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide gel electrophoresis followed by sodium dodecyl sulfate gradient polyacrylamide gel electrophoresis for the study of the dimer to monomer transition of human transthyretin

Abstract: Familial amyloidotic polyneuropathy (FAP) is caused by mutations which destabilize transthyretin (TTR) and facilitate the aggregation into extracellular amyloid fibrils preferentially in peripheral nerve and heart tissues. Therapeutic and preventive trials for FAP at the plasma TTR level require a careful study of the destabilization of TTR under variable conditions. We have developed a simple double one-dimensional (D1-D) electrophoretic procedure with polyacrylamide gel electrophoresis (PAGE) followed by sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Therefore, we analysed the relative amounts of TTR monomers and dimers in FAP and control subjects by SDS-PAGE, as previously used to evaluate the relative amount of TTR dimer to monomer species [44]. Also, the stable sample-specific dimer/monomer ratios, achieved under conditions of partial dimer to monomer transition, reflect the conformational monomer stability relative to the dimeric form [45]. Once a dimer dissociates, the monomers are captured in a complex with SDS and their ability to associate as a dimer is compromised.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we analysed the relative amounts of TTR monomers and dimers in FAP and control subjects by SDS-PAGE, as previously used to evaluate the relative amount of TTR dimer to monomer species [44]. Also, the stable sample-specific dimer/monomer ratios, achieved under conditions of partial dimer to monomer transition, reflect the conformational monomer stability relative to the dimeric form [45]. Once a dimer dissociates, the monomers are captured in a complex with SDS and their ability to associate as a dimer is compromised.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, native TTR only accounts for 5$15% of total TTR circulating in plasma. The other 85$95% is posttranslationally modified in the forms of S-sulfonation and S-thiolation [Altland and Winter, 2003]. Importantly, it has been reported that the levels of TTR could decrease in cases of severe liver disease, malnutrition, and acute inflammation [Imanishi, 1981;Marten et al, 1996;Ritchie et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…2A). The differential expressed band at $16 kDa could very possibly be the protein corresponding to peaks observed on chips, for the reason that migration rates for proteins with molecular masses less than 20 kDa may become more dependent on differences of structural features than of masses [Altland and Winter, 2003]. To confirm the doubt, differential expression band at about $16 kDa was excised from the gels for trypsin digestion and identified by ESI-MS/MS.…”
Section: Identification Of $16 Kda Differential Band Between Cholangimentioning
confidence: 99%
“…The diagnosis of TTR amyloidosis was verified by clinical symptoms, identification of amyloid in biopsy specimens by appropriate staining (plus immunohistochemical identification of TTR in some cases) and the identification of a TTR mutation by DNA analysis. PAGE followed by IEF in urea gradients or by SDS gradient PAGE was performed as described [3,5]. Gels with IPG ranging from pH 4.2 to 6.8 over distance of 12 cm were used for IEF.…”
Section: Methodsmentioning
confidence: 99%